A Featural Typology of Bantu Agreement - van der Wal, Jenneke (Oxford University Press, 2022)
The Bantu languages are in some sense remarkably uniform (SVO basic word order, noun classes, verbal morphology), but this extensive language family also show a wealth of morphosyntactic variation. Two core areas in which such variation is attested are subject and object agreement. The book explores the variation in Bantu subject and object marking on the basis of data from 75 Bantu languages, discovering striking patterns (the RANDOM and the AWSOM correlation), and providing a novel syntactic analysis. This analysis takes into account not just phi agreement, but also nominal licensing and information structure. A Person feature, associated with animacy, definiteness, or givenness, is shown to be responsible for differential object agreement, while at the same time accounting for doubling vs. non-doubling object marking - a hybrid solution to an age-old debate in Bantu comparative morphosyntax. It is furthermore proposed that low functional heads can Case-license flexibly downwards or upwards, depending on the relative topicality of the two arguments involved. This accounts for the properties of symmetric object marking in ditransitives (for Appl), and subject inversion constructions (for v). By keeping Agree constant and systematically determining which featural parameters are responsible for the attested variation, the proposed analysis argues for an emergentist view of features and parameters (following Biberauer 2018, 2019), and against both Strong Uniformity and Strong Modularity.